Lebanon : Report on Performance Under the Program Supported by Emergency Post; Conflict Assistance. (IMF Staff Country Reports; Country Report ;, 2008)
The economic performance of Lebanon was significantly better despite difficult political conditions under the Emergency Post-Conflict Assistance (EPCA). With lackluster growth and fiscal tightness, the external current account deficit needs to be improved. There is limited scope for fiscal policy actions. The government faces substantial gross financing needs and remains vulnerable to changes in regional liquidity and demand. Increased inflation could worsen the fiscal outlook. In view of this, the authorities have expressed interest in continued quarterly monitoring of Lebanon's economic policies and performance by the IMF.